Understanding the Added Value of G-Protein-Coupled Receptor Heteromers - Nuria Franco; Rafael Franco (Scientifica)
G-protein-coupled receptors (GPCRs) constitute the most populated family of proteins within the human genome. Since the early sixties work on GPCRs and on GPCR-mediated signaling has led to a number of awards, the most recent being the Nobel Prize in Chemistry for 2012. The future of GPCRs research is surely based on their capacity for heteromerization. Receptor heteromers offer a series of challenges that will help in providing success in academic/basic research and translation into more effective and safer drugs.